Interaction model of agribusiness: the case of tomato farming in West Java. (21st September 2020) - Okdinawati, Liane; Sunitiyoso, Yos; Simatupang, Togar M.; Hermawan, Pri; Noerhatini, Pathmi; Sitadewi, Dania
The importance of the Indonesian agriculture supply chain lies in the vision of the national government with regard to food security and farmer welfare which supports the production of various healthy types of food and high value-added products utilising local resources. However, local agricultural products face certain inefficient business practices, due to the involvement of multi-layer parties in the distribution network, which serves the ultimate consumers. Previous studies involving research into agriculture only provide a partial description of both conventional agriculture and the organic agricultural supply chains. Therefore, this paper attempts to provide a comprehensive description of all agribusiness parties by reproducing the agricultural product supply chain network operating under prevailing conditions in West Java, Indonesia, using tomato products as a case study. This paper analyses two types of tomato agribusiness, conventional and organic, in order to identify possible differences in the supply chain process and their contrasting interactions. The value system method is examined to highlight the dynamics of the interrelationship between several participating parties.